'The Primacy of 'Home': An exploration of how older adults' transition to life in a care home towards the end of the first year. (26th November 2020) - O'Neill, Marie; Ryan, Assumpta; Tracey, Anne; Laird, Liz
Abstract: This grounded theory study sought to explore how older adults' experience the transition from living at home to a care home with a specific focus on the latter part of the first year of the move. The study was carried out within a large Health Trust in the UK between August 2017 and May 2019. Purposive sampling was used in the initial stages of data collection. Thereafter and consistent with grounded theory methodology, theoretical sampling was employed to undertake semi‐structured interviews with 17 individuals from eight care homes between 5 and 12 months after the move. This paper reports five key categories which were: (a) The lasting effect of first Impressions ' They helped me make my mind up' (b) On a Journey ' I just take it one day at a time', (c) Staying connected and feeling 'at home' ' You get something good out of it you know…you get hope' . (d) Managing loss and grief ' It was important for me to say cheerio to the house' and (e) Caring relationships ' I didn't realise that I was lonely until I had company' . Together these five categories formed the basis of the core category 'The Primacy of 'Home' which participants identified as a place they would like to feel valued, nurtured and have a sense of belonging. This study identifies that it is important for individual preferences and expectations to be managed from the outset of the move. Individuals and families need to be supported to have honest and caring conversations to promote acceptance and adaptation to living in a care home while continuing to embrace the heart of 'home'. Key recommendations from this study include the need to raise awareness of the significance of the ongoing psychological and emotional well‐being needs of older people which should be considered in policy directives and clinical practice.